Cost Evaluation and Economic Sustainability of Enzyme Replacement Therapies for Fabry Disease in Italy from the Hospital Perspective - Ghetti, Gianni; Spiombi, Eleonora; Amoroso, Lucrezia; Viti, Raffaella; Spada, Marco (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
BACKGROUND AND AIM: Fabry disease is a rare X-linked lysosomal hereditary disease caused by pathogenic variants in the GLA gene that results in deficient α-galactosidase A enzyme activity. Enzyme replacement therapy (ERT) remains a primary approach to address the enzymatic defect and its pathophysiological impacts. This study aimed to evaluate the annual treatment costs associated with agalsidase alfa, agalsidase beta and pegunigalsidase alfa within the context of the Italian National Healthcare Service (NHS).METHODS: A cost comparison model was developed to estimate the treatment-related expenditure for agalsidase alfa, agalsidase beta, and pegunigalsidase alfa over 1-year time horizon from the hospital perspective. The analysis accounted for drug acquisition and administration costs across hospital-based, home-based, and self-administration settings. Infusion durations were estimated based on product specifications and patient characteristics from published literature. Costs were calculated using adjusted ex-factory list prices and literature-sourced hourly rates for healthcare professionals. Expert validation ensured model accuracy, and sensitivity analyses examined the impact of varying infusion scenarios.RESULTS: In the base case, agalsidase alfa demonstrated the lowest annual treatment cost (€172,395), followed by pegunigalsidase alfa (€173,744), while agalsidase beta incurred the highest cost (€191,143). Scenario analysis confirmed that agalsidase alfa offers a more sustainable alternative compared to agalsidase beta, while demonstrating comparable costs to pegunigalsidase alfa. Furthermore, the analysis indicated that variations in infusion settings had impact on overall outcomes, depending on the home or hospital preference.CONCLUSION: This economic evaluation suggests that agalsidase alfa may offer cost advantages relative to other ERTs, particularly in comparison to agalsidase beta. These advantages are primarily driven by lower annual treatment costs. In addition, agalsidase alfa’s unique approval for self-administration in Italy, has the potential to reduce healthcare expenditures, optimizing hospital resource allocation, and enhancing the efficiency of healthcare delivery for patients with Fabry Disease.